Stone kiss - Kellerman, Faye (Kellerman, Faye. Decker/Lazarus novel., 2002)
'It was the stunned, pale look of bad news' The call was from Rabbi Jonathan Levine, Decker's recently discovered half brother. There has been a murder in Jonathan's family; his brother-in-law, a Hassidic Jew and former drug addict, was found naked in a seedy Manhattan hotel, a single gunshot wound to his head. And his niece, fifteen-year-old Shaynda, is missing... In a desperate bid to track down the missing girl, Decker finds himself in an alien city and a maze of deceit and danger, on a twisted journey that takes him from the darkened slums of New Jersey and the deserted industrial streets of New York, to the hidden meeting places of Hassidic outcasts...